Taste of cherry Tam e guilass - Kiarostami, Abbas; Ershadi, Homayoun; Bagheri, Abdolhossein; Bakhtiari, Afshin; Noori, Mir Hossein; Moradi, Safar Ali (Criterion collection ;, 1999)
Mr. Badii, ceaselessly driving through the red-brown hills around Tehran in search of assistance in his suicide, receives from each of the men he asks for help a viewpoint on life.